Nonclinical Safety Assessment of the γ-Secretase Inhibitor Avagacestat. (24th February 2018) - Simutis, Frank J; Sanderson, Thomas P; Pilcher, Gary D; Graziano, Michael J
Abstract: The toxicity of avagacestat, a sulfonamide-based gamma (γ)-secretase inhibitor that was in development as a treatment for Alzheimer's disease, was evaluated in a comprehensive nonclinical toxicology program that included 6-month and 1-year repeat-dose toxicity studies in rats and dogs, respectively. There was a spectrum of mechanism-based changes attributed to inhibition of Notch signaling that regulates the differentiation and proliferation of cells throughout development and in adult tissues. In both rats and dogs, ovarian follicular degeneration and atrophy and a low incidence of granulosa cell hyperplasia and benign granulosa-thecal cell tumors were observed. Gastrointestinal (GI) findings, including goblet cell metaplasia, dilatation of intestinal crypts/glands, mucosal epithelial necrosis and regeneration, and villous atrophy, were limited to dogs that had clinical evidence of GI toxicity. Other avagacestat-related findings attributed to interference with Notch signaling included decreases in peripheral lymphocytes (T and/or B cells) and lymphoid depletion in lymph nodes and the spleen in both species, as well as epiphyseal cartilage and trabecular bone changes in rats. Pharmacologically mediated decreases in brain and cerebrospinal fluid levels of β-amyloid (Aβ) peptides Aβ40 and Aβ42 and decreased expression of white blood cell mRNA levels of the Notch-regulated gene hairy and enhancer of split-1 confirmed target engagement at all doses. Reductions in brain Aβ peptide levels (22 to 34%) in dogs after 1 year at exposures up to the no-observed-effect level for GI toxicity of 1.1× the human plasma exposure, and reversible GI changes at a 3.2× multiple, indicated that a sustained pharmacodynamic effect was attained at exposures without dose-limiting toxicity.